Backmapping triangulated surfaces to coarse-grained membrane models - Weria Pezeshkian (Nature Portfolio, 2020)
Computer simulations of large-scale changes in membrane shape are challenging since they occur across a wide range of spatiotemporal scales. Here, authors present a multiscale algorithm that backmaps a continuum membrane model represented as a dynamically triangulated surface to its corresponding molecular model based on the coarse-grained Martini force field.